Evaluation of maize (Zea mays) cultivars under organic production system in north-western Indo-Gangetic Plains of India - N K JAT; SUDHIR KUMAR; M SHAMIM; SUBHASH BABU; N RAVISANKAR; A S PANWAR (The Indian Journal of Agricultural Sciences, 2019)
Increased awareness of environmental degradation and growing concern of human health has attracted worldwide attention towards organic farming. A field experiment was carried out during kharif of 2013–2014 to identify suitable maize (Zea mays L.) cultivars having high yield potential under organic production system. Twelve released cultivars of maize varied in duration and nitrogen requirement were evaluated. Results revealed that late maturing cultivars PMH-1 and PMH-3 being at par to each other recorded the significantly higher values of growth parameters like plant height, dry matter accumulation and leaf area index; and yield attributes in terms of cobs plant, cob length, cob girth, grain rows/cob, grains/row and test weight, whereas the extra early cultivars like Vivek QPM-9 being at par with Vivek Hybrid-9 registered the lowest values of growth and yield attributes. The late maturing cultivars like PMH-1, PMH-3, Seed tech-2324 and Bio-9681 produced significantly higher grain yield (>5.0 t/ha) and biological yield (>12.5 t/ha). Cultivars PMH-4 among medium maturity group produced comparable yield with late cultivars. Grain yield across the varied duration cultivars had a significant positive correlation with cob length, grains/row and N uptake. As per their maturity class, the extra early and early cultivars commence silking (<50 days) and physiological maturity (<82 days) significantly earlier than medium and late cultivars. Moreover, extra early cultivars (Vivek Hybrid-9 and Vivek QPM-9) recorded significantly higher protein content in grain amongst the cultivars tested. The late cultivars PMH-1 and PMH-3 being at par with each other recorded the highest N, P and K uptake in plants while lowest nutrient uptake was observed in the extra early Vivek QPM-9 and Vivek Hybrid-9. Late cultivar PMH-3 followed by PMH-1 recorded the highest net returns (` 66,759) and B:C ratio (1.79) of organic maize cultivation. Soil fertility status in terms of organic carbon, available P and K could not be influenced significantly, however the available N content was significantly higher under extra early cultivars Vivek QPM-9 (172.1 kg/ha) and Vivek Hybrid-9 (170.3 kg/ha). Thus, it can be concluded that PMH-1 and PMH-3 cultivars of maize are most suitable for growing in north-western plains region of Uttar Pradesh under organic production system.